2014
DOI: 10.1051/0004-6361/201322631
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Milky Way stellar disk

Abstract: Aims. The aim of this paper is to explore and map the age and abundance structure of the stars in the nearby Galactic disk. Methods. We have conducted a high-resolution spectroscopic study of 714 F and G dwarf and subgiant stars in the Solar neighbourhood. The star sample has been kinematically selected to trace the Galactic thin and thick disks to their extremes, the metal-rich stellar halo, sub-structures in velocity space such as the Hercules stream and the Arcturus moving group, as well as stars that canno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

231
1,628
30
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,063 publications
(1,891 citation statements)
references
References 108 publications
231
1,628
30
2
Order By: Relevance
“…There is an indication that almost all the OCs older than 1 Gyr yield slightly more positive [α/Fe] ratios for both thin and thick disc samples than those represented by younger ages. A similar behaviour is observable for Galactic field stars where the older thin and thick disc field dwarfs from Bensby et al (2014) yield more positive [α/Fe] ratios than the younger field dwarfs with thin disc kinematics. The similarity in [α/Fe] between the thin and thick disc clusters with ages of 4 to 9 Gyr suggest that age cannot be the key variable, but different proportions of Type II to Type Ia supernovae products in clusters formed at dif- Adibekyan et al 2013;Bensby et al 2014).…”
Section: [α/Fe] Vs Cluster's Agesupporting
confidence: 73%
See 1 more Smart Citation
“…There is an indication that almost all the OCs older than 1 Gyr yield slightly more positive [α/Fe] ratios for both thin and thick disc samples than those represented by younger ages. A similar behaviour is observable for Galactic field stars where the older thin and thick disc field dwarfs from Bensby et al (2014) yield more positive [α/Fe] ratios than the younger field dwarfs with thin disc kinematics. The similarity in [α/Fe] between the thin and thick disc clusters with ages of 4 to 9 Gyr suggest that age cannot be the key variable, but different proportions of Type II to Type Ia supernovae products in clusters formed at dif- Adibekyan et al 2013;Bensby et al 2014).…”
Section: [α/Fe] Vs Cluster's Agesupporting
confidence: 73%
“…A similar behaviour is observable for Galactic field stars where the older thin and thick disc field dwarfs from Bensby et al (2014) yield more positive [α/Fe] ratios than the younger field dwarfs with thin disc kinematics. The similarity in [α/Fe] between the thin and thick disc clusters with ages of 4 to 9 Gyr suggest that age cannot be the key variable, but different proportions of Type II to Type Ia supernovae products in clusters formed at dif- Adibekyan et al 2013;Bensby et al 2014). Although the origin of such objects is still in debate, Adibekyan et al (2011Adibekyan et al ( , 2013 have suggested a possible origin of these α-enhanced metal-rich stars in the inner Galaxy (bulge) followed by a subsequent migration to the solar vicinity.…”
Section: [α/Fe] Vs Cluster's Agesupporting
confidence: 73%
“…2, since the scatter is still relatively high. Nevertheless, the work by Bensby et al (2014) claimed that thin and thick disc stars potentially exhibit two separate abundance trends, especially in the range −0.7 [Fe/H] −0.35 dex, expected by the authors also in the unpublished GAIA data.…”
Section: Free Parameters and Methodsmentioning
confidence: 64%
“…In F-, G-, and K-type stars whose photospheric continua are well-defined in high-resolution spectra, stellar metallicity is computed through spectral synthesis (McWilliam 1990;Valenti & Piskunov 1996;González 1997;González Hernández et al 2004;Valenti & Fischer 2005;Recio-Blanco et al 2006) or measuring equivalent widths, especially of iron lines (Sousa et al 2008(Sousa et al , 2011Magrini et al 2010;Adibekyan et al 2012;Tabernero et al 2012;Bensby et al 2014). However, it is not possible to measure a photospheric continuum in M-type stars and, thus, their metallicity is studied through other techniques.…”
Section: Metallicitymentioning
confidence: 99%